(untitled) (Sahayaatra सहयात्रा, 2025)
In Nepal’s developing stock market, stock prices are not always determined by a company’s actual performance or economic indicators. Instead, investor emotions, market rumors, and collective behavior often have a stronger influence. This study explores the influence of psychological and emotional factors, including herd behavior, overconfidence bias, loss aversion, and overreaction or underreaction to news, as well as overall market sentiment and speculation, on stock price movements. The main objective is to examine the short-term relationship between investor sentiment and daily stock price changes. Unlike previous studies in Nepal that focused mainly on technical and financial data, this research highlights real-time emotional influences using 15 days of daily data from the Nepal Stock Exchange (NEPSE), covering one listed company from each of 11 different sectors. Descriptive statistics, correlation, regression analysis, and ANOVA were used to assess the data. The results showed that herd behavior is weakly positively correlated with stock prices, while overreaction and loss aversion have a moderate effect. Overconfidence and market sentiment had relatively weaker impacts. The regression analysis finds a multiple R value of 0.3946, showing a weak positive relationship. The R-squared value indicates that only 15.57% of the variation in stock prices can be explained by these sentiment factors. The adjusted R-squared is even lower at 0.0978. The F-value was 0.3319, with a significance level of 0.8814, which is far above the standard 0.05 threshold. This means the model as a whole is not statistically significant. These findings suggest that while emotional and psychological factors may influence investor behavior, they did not have a strong or consistent impact on stock price changes during the short period studied. Still, recognizing these behavioral patterns is important for investors and policymakers, as emotional trading can lead to unexpected market movements. This study encourages further research with longer timeframes and broader data to better understand the role of investor sentiment in Nepal’s financial market.